2014
DOI: 10.1002/ps.3746
|View full text |Cite
|
Sign up to set email alerts
|

Resistance to herbicides inhibiting the biosynthesis of very‐long‐chain fatty acids

Abstract: Herbicides that act by inhibiting the biosynthesis of very-long-chain fatty acids (VLCFAs) have been used to control grass weeds in major crops throughout the world for the past 60 years. VLCFA-inhibiting herbicides are generally highly selective in crops, induce similar symptoms in susceptible grasses and can be found within the herbicide groups classified by the HRAC as K3 and N. Even after many years of continuous use, only 12 grass weed species have evolved resistance to VLCFA-inhibiting herbicides. Here, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
66
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 52 publications
(68 citation statements)
references
References 84 publications
1
66
0
1
Order By: Relevance
“…A large geographical survey conducted in 2010 across the Western Australian grain belt reported >95% frequency of multiple resistance to ACCase‐ and ALS‐inhibiting herbicides in L. rigidum . One response to resistance and failures of post‐emergent herbicides has been the adoption of pre‐emergent herbicides, especially prosulfocarb, pyroxasulfone and trifluralin . An increasingly common practice has been the use of herbicide mixtures of trifluralin and pyroxasulfone, trifluralin and prosulfocarb or trifluralin and triallate.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A large geographical survey conducted in 2010 across the Western Australian grain belt reported >95% frequency of multiple resistance to ACCase‐ and ALS‐inhibiting herbicides in L. rigidum . One response to resistance and failures of post‐emergent herbicides has been the adoption of pre‐emergent herbicides, especially prosulfocarb, pyroxasulfone and trifluralin . An increasingly common practice has been the use of herbicide mixtures of trifluralin and pyroxasulfone, trifluralin and prosulfocarb or trifluralin and triallate.…”
Section: Discussionmentioning
confidence: 99%
“…However, as we found partial synergistic interaction between phorate and pyroxasulfone, we suggest (1) that phorate was partially effective in inhibiting putative P450 enzymes mediating pyroxasulfone metabolism or (2) that pyroxasulfone resistance, evolved in MR by low‐dose recurrent pyroxasulfone selection, was probably only partially mediated by enhanced cytochrome P450 metabolic activity on pyroxasulfone. The involvement of GSTs mediating herbicide detoxification via glutathione conjugation is well documented for chloroacetamide and thiocarbamate herbicides (reviewed elsewhere). One study reported evidence of high levels of GST‐mediated pyroxasulfone metabolism in wheat versus low levels in L. rigidum plants to explain the herbicide selectivity in crops versus efficacy on weeds respectively …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, since the first report of an Australian weed population resistant to diclofop, ACCase post‐emergence herbicide resistance has increased widely across the Australian grainbelt. In contrast, the evolution of resistance to pre‐emergence herbicides has been slower, and some pre‐emergence herbicides have remained largely effective, despite, in some cases, decades of frequent use across extensive areas …”
Section: Introductionmentioning
confidence: 99%